Effect of chia (Salvia hispanica l.) on the bioavailability of minerals, lipid profile, inflammation, oxidative stress, and intestinal health - Silva, Bárbara Pereira da (2019)
Chia is a pseudocereal that consumed worldwide due to its protective, functional and antioxidant effects, attributed to the presence of lipids, dietary fiber, antioxidant compounds, vitamins and minerals. Among the minerals, calcium, iron and zinc can be highlighted. But although present in good concentration, the bioavailability of these nutrients is unknown. Also, the effect of chia consumption on inflammatory markers and oxidative stress is not known in animals fed a high-fat diet. Furthermore, the effects of intra-amniotic administration of prebiotics extracted from chia on the morphology and functionality intestinal, on intestinal microbiota and on iron and zinc status are not known. In this sense, the objective of the study was to evaluate the effect of chia (Salvia hispanica L.) flour consumption on the bioavailability of calcium, iron and zinc, lipid profile, inflammation, oxidative stress, intestinal functionality and morphology, and intestinal microbiota. Chia flour cultivated in Brazil (RS state) was used. To obtain the flour, the seeds were ground. In the first biological essay (Manuscript 1), the effect of chia consumption on calcium bioavailability, inflammation, oxidative stress was conducted during 7 weeks. Thirty-two 21-day-old male Wistar rats were given either the AIN-93G diet or the high-fat diet. The study consisted of 4 experimental groups: AIN-93G + calcium carbonate, AIN-93G + chia, high-fat diet + calcium carbonate and high-fat diet + chia. The effects of chia intake on calcium bioavailability were measured using the calcium balance technique. In addition, the effect of chia flour on biochemical markers, inflammation and oxidative stress was evaluated. Chia presented low calcium bioavailability, regardless of the type of diet consumed. However, chia consumption reduced inflammatory processes, improved lipid profile and had no effect on oxidative stress. In the second biological essay (Manuscript 2), the effect of chia consumption on oxidative stress and inflammation in ovariectomized adult rats was evaluated. Eighty 21-day-old female Wistar rats were used. The animals received AIN93-G diet (n = 40) or high fat diet (n = 40) for 7 weeks. At week seven, 40 rats underwent ovariectomy (OVX) and 40 rats underwent surgery, but without organ removal (SHAM). The animals remained in these groups for 3 weeks to recover from surgery. Thus, after 10 weeks, the animals were relocated to the following eight experimental groups, where they remained receiving the experimental diets for 8 weeks: 1) control diet (SHAM), 2) high fat diet (SHAM), 3) control diet + chia (SHAM), 4) high fat diet + chia (SHAM), 5) control diet (OVX), 6) high fat diet (OVX), 7) control diet + chia (OVX), 8) high fat diet + chia (OVX). After 18 weeks, the animals were euthanized. Gene expression of protein related to inflammation and oxidative stress were measured. It was evaluated chia consumption on biochemical markers. Intake of chia improved lipid profile and increased hepatic and cecal indexes. In addition, chia consumption associated with the standard diet improved antioxidant activity, increased SOD and PPAR-α gene expression, and catalase activity, while reducing NFκB expression. Chia consumption associated with high fat diet in ovariectomized rats reduced IL-1β levels and TNF-α expression, increased SOD expression and concentration, and catalase activity. In the third study (Manuscript 3), we evaluated the effect of intra-amniotic administration of prebiotics extracted from chia on gene expression of proteins related to iron and zinc metabolism, as well as effect of prebiotic on intestinal functionality, intestinal morphology and bacterial population in a broiler model (Gallus gallus). The concentration of dietary fiber and phenolic compounds in chia flour was evaluated. Seven experimental groups were used (Group 1: non- injected; Group 2: 18MΩH2O; Group 3: 40mg/mL Inulin; Group 4: 0.5% chia; Group 5: 1% chia; Group 6: 2.5% chia; Group 7: 5% chia). The gene expression of iron and zinc-related proteins was performed by RT-qPCR as well as the expression of brush border membrane proteins and the bacterial composition was evaluated by PCR. Measurements of villi and crypts as well as the number and diameters of goblet cell were evaluated by histological techniques. Intra-amniotic administration of soluble chia extract improved intestinal morphology and protein expression related to Zn metabolism. In addition, chia soluble extract improved gene expression of proteins related to iron metabolism. The consumption of chia demonstrated improve intestinal health and contribute to the absorption of minerals. Thus, in general, our results demonstrated that chia was capable to improve the lipid profile, inflammatory process, oxidative stress, intestinal morphology, intestinal functionality and intestinal microbiota, in vivo. In addition, the consumption of this food had low bioavailability of minerals, such as, calcium. Keywords: Bone metabolism. Calcium. Inflammatory process. Intestinal microbiota. Iron. Zinc.